EVALUATING THE EFFECTIVENESS OF SONG-BASED INSTRUCTION IN EARLY YEARS AE CLASSROOMS: EXTENDING MILLINGTON’S FRAMEWORK. - Dildora Radjabova, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation:  Song-based  instruction  is  a  staple  of  early  years  language education, yet its implementation often lacks a rigorous pedagogical framework. This article evaluates the effectiveness of songs in Accelerated English (AE) classrooms by extending  Millington’s  (2011)  tripartite  framework—preparation,  core  activity,  and follow-up.  While  Millington  focused  primarily  on  vocabulary  acquisition,  this extension  incorporates  elements  of  pronunciation,  listening  comprehension,  and affective  filter  reduction.  Through  a  review  of  current  literature  and  a  proposed methodological approach, the study finds that structured song-based tasks significantly improve student engagement and retention compared to passive listening.